PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI MODEL PEMBELAJARAN SCRAMBLE PADA PEMBELAJARAN BAHASA INDONESIA - Maharani, Anggun; Fauziddin; Marleni, Lusi; Marta, Rusdial; Mufarizuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is based on the low results of students' reading comprehension skills in grade IV UPT SDN 004 Birandang Island. One solution to overcome this problem is to use the Scramble learning model. The purpose of this research is to improve students' reading comprehension skills in Indonesian language learning chapter 3 of the Around View. This research method is a class action research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The research time will be carried out in November 2025. The subjects of this study are 14 grade IV students, consisting of 7 male students and 7 female students. Data collection techniques are in the form of observation, tests and documentation. The results of this study can be concluded that the results of students' reading comprehension skills in the material of chapter 3 See Around in grade IV UPT SDN 004 Birandang Island pre-action an average score of 42.86 with a classical completeness of 14.28%, then in the first cycle meeting 1 has increased to 44.64 with a classical completeness of 21.42%, and in the first cycle of meeting 2 it has increased to 64.28 with classical completeness of 42.85%. Furthermore, in the second cycle of meeting 1, an average score of 79.01 was obtained with a classical completeness of 71.42%, and in the second cycle of meeting 2, an average score of 89.73 was obtained with classical completeness of 100%. Thus, it can be concluded that students' reading comprehension skills can be improved by applying the Scramble model.